Potiphar’s Wife in David’s Looking Glass Reading 2 Samuel 11-12 as a Reflection Story of Genesis 39 - Postell, Seth D. (2020)
Though the parallels between Joseph and David have been well noted, the numerous literary links between Joseph’s exemplary behaviour with Potiphar’s wife on the one hand and David’s disgraceful behaviour with Bathsheba on the other has gone by largely unnoticed. In this article, we analyse 2 Samuel 11–12 as a reflection story of Genesis 39, noting the numerous parallels and striking contrasts. Given the many allusions to Joseph in 1 Samuel, the reader expects to see only Joseph’s reflection in David’s mirror in 2 Samuel 11–12, but finds Potiphar’s wife looking back at David as well.
Keywords: Adultery; Biblical teaching; Allusions in the Bible; Bathsheba, (Biblical figure); Bible. Genesis; Criticism, Narrative; Bible. Samuel II; Criticism, Narrative; David, King of Israel; Intertextuality in the Bible; Joseph, (Biblical patriarch); Potiphar's wife, (Biblical figure)